Distinguishing Characteristics and Disparities in Child Protective Services-Investigated Maltreatment by Fathers. (May 2021) - Kobulsky, Julia M.; Wildfeuer, Rachel; Yoon, Susan; Cage, Jamie
This study examines distinguishing characteristics of father-perpetrated maltreatment and disparities in Child Protective Services (CPS) investigation outcomes based on perpetrator gender and race. A sample of children ( N = 2, 017) reported to CPS for maltreatment attributed to their mother and/or father was drawn from the second National Survey of Child and Adolescent Well-being (NSCAW II). Measures included perpetrator(s) relationship to the child (mother alone, father alone, mother and father) and race (Black, White, Other), caseworker-reported maltreatment characteristics and co-occurring risk factors, and CPS investigation outcomes (services, substantiation, out-of-home placement, criminal investigation, and criminal charges). Bivariate analyses revealed no clear pattern of higher risk for maltreatment involving fathers. In regression, father-alone perpetration predicted less out-of-home placement but more criminal investigations and charges. A significant interaction indicated the greatest risk for criminal charges when a Black father co-perpetrated maltreatment with mother. Findings imply needs for anti-bias training, specialized services for fathers, and coordinated diversion between child welfare and criminal justice systems.